Syllable cut and energy contour in vowels: a comparative study on German and Hungarian - Mády, Katalin; Tronka, Krisztián; Reichel, Uwe D. (ZAS Papers in Linguistics, 2005)
Syllable cut is said to be a phonologically distinctive feature in some languages where the difference in vowel quantity is accompanied by a difference in vowel quality like in German. There have been several attempts to find the corresponding phonetic correlates for syllable cut, from which the energy measurements of vowels by Spiekermann (2000) proved appropriate for explaining the difference between long, i.e. smoothly, and short, i.e. abruptly cut, vowels: in smoothly cut vowels, a larger number of peaks was counted in the energy contour which were located further back than in abruptly cut segments, and the overall energy was more constant throughout the entire nucleus. On this basis, we intended to compare German as a syllable cut language and Hungarian where the feature was not expected to be relevant. However, the phonetic correlates of syllable cut found in this study do not entirely confirm Spiekermann's results. It seems that the energy features of vowels are more strongly connected to their duration than to their quality.